It Is Just a Rash They Said! Acute Skin Manifestation in a Patient With Vasculitis in Rural Hospitals - Khalid Sawalha MD; Anthony Kunnumpurath MBBS; Shailendra Singh MD, FACP; Gilbert-Roy Kamoga MD, FACP (SAGE Publishing, 2020)
A 76-year-old Caucasian male with a history of rheumatoid arthritis, Raynaud's phenomenon, pulmonary embolism on warfarin, and a previous amputation of his left partial ring and fifth finger presented with acute onset of rash in bilateral lower extremities. He was recently started on trimethoprim-sulfamethoxazole due to concern for cellulitis. Differential diagnosis for acute-onset rash with the patient's history presented as a challenge to the internist, as the differential is broad. Our case goes through the differential diagnosis to contrast the different presentations of rash in a patient with vasculitis. Ultimately skin biopsy in conjunction with a past positive cryoglobulinemic level helped confirm the diagnosis of cutaneous vasculitis, following which he was started on appropriate treatment and recovered.